Isolation, characterization, and proteomic analysis of plasma-derived extracellular vesicles for cardiovascular biomarker discovery - Trauner, Gabriel Jakob; Bernáth-Nagy, Dominika; Kalinyaprak, Melek Sükran; Merker, Sabine; Luzarowski, Marcin; Leuschner, Florian; Frey, Norbert; Giannitsis, Evangelos; Krohn, Jona B. (JoVE. Video journal, 2025)
Extracellular vesicles (EV) are cell-derived, lipid bilayer-enclosed, non-replicable nanoparticles. EV currently gain attention in cardiovascular research due to their role in regulating intercellular communication, potentially serving as valuable biomarkers for cardiovascular disease. However, the EV proteome and its potential as a biomarker in cardiovascular diagnostics remain poorly understood. This protocol presents a standardized method for the isolation and quantification of plasma-derived EV and the analysis of their protein cargo using plasma samples from patients presenting to the Chest Pain Unit of a large university hospital. Following routine phlebotomy, EV are isolated from plasma by differential ultracentrifugation. The enrichment of specific EV marker proteins in EV isolates is visualized by immunoblotting, and average size distribution and plasma EV concentrations are quantified by nanoparticle tracking analysis. Finally, ultra-performance liquid chromatography-tandem mass spectrometry is employed for label-free analysis of the EV proteome. This protocol thus provides a comprehensive approach to study and use plasma-derived EV as potential carriers of critical biological information as well as to explore their potential as novel biomarkers.
Enthält auch Textversionen
Gesehen am 23.10.2025
Wissenschaftlicher Film. Deutschland. 2025
Keywords: Film